Analysis Of Behavior And Sosio-Economic Impact Of Relocation Of Street Vendors During The Covid-19 Pandemic - Sinta Putri Janah; Hendri Hermawan Adinugraha (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2021)
Abstract Street vendors are an alternative to businesses in the informal sector with relatively small capital to support their needs. In meeting our daily needs, we definitely need income or income. therefore, we need a job which is to support our needs. The purpose of this study is to describe the behavior of street vendors in the perspective of Islamic business ethics and to describe the socio-economic conditions of relocation of street vendors before and after the Covid-19 pandemic. The research design used is descriptive discussion. Data were collected by using in-depth interviews, observation, and documentation methods. Data were analyzed using qualitative methods. The results of the study show that the behavior of street vendors is in accordance with Islamic business ethics. The impact of the socio-economic conditions of street vendors has recently undergone many changes due to the implementation of relocation. The income of traders has decreased on average, especially since the Covid-19 pandemic, and even then some of them have changed their profession.